Analysis of community based industrial waste treatment to control river water pollution - Nurwahdah; Farhan, Rifky; Alfarizi, M. Ardievo; Gusti, Utari Akhir (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Body parts Diverse minerals and chemical substances found in water play a crucial role in the survival and ecosystem-wide equilibrium of aquatic life. Modernization and development aimed at enhancing human quality of life have, however, had a negative impact on the natural state of waters due to an increase in the number and quality of compounds. There are various challenges currently facing waste management as part of environmental rehabilitation efforts. The population has developed a habit of disposing of waste into river streams, and their unwillingness to treat it also contributes to the main issue, as was the case in the Padang River Stream Area. Water that is contaminated In this case the method used in this study is to collect data on survey results localized to the procedure: an unstructured interview, (guideline study only includes the important questions problem to be dug out of the respondents), so it can produce primary data , which will be the subject of research, and Non-Participant observation (observation that the researcher did not participate directly in the activities that are being observed), which produces secondary data that will strengthen the primary data. In this situation, the study's findings are anticipated to offer the best method for reducing Padang River pollution.